Wireless Communication as a Reshaping Tool for Internet of Things (IoT) and Internet of Underwater Things (IoUT) Business in Pakistan: A Technical and Financial Review - Rizvi, S.S.H. (Springer, 2021)
Pakistan is one of the growing nations, specifically in the field of Information and Communication Technology (ICT). During the last decade, an intense rise in the adaptation of ICT has been observed in all the major cities of Pakistan. This includes, but not limited to, e-commerce, mobile technology, computer communication networks, embedded systems, software engineering, etc. Due to the resource constraints, Pakistan is not the producer of any technology; however, it is a potential consumer of numerous technologies and their products. It therefore, attracts most of the producers around the globe to invest in the technology business in Pakistan. According to the Board of Investment (BOI) Pakistan, the country has received more than US5.7 billion during the last decade as the foreign investment in IT and Telecommunication sectors only. Moreover, it has more than 140 million cellular subscribers, around 45 million 3G/4G subscribers, more than 3 million fixed local line subscribers and approximately 48 million broadband subscribers 1. Likewise, Pakistan is also one of the biggest buyers of Consumer Electronics (CE). Very few of the local companies are producing CE products, however, a major share of the CE market has been captured by the international brands of China, Japan, Korea, USA, Germany, etc. In the light of the facts, it can be inferred that the application of ICT such as the Internet of Things (IoT) and Internet of Underwater Things (IoUT) in consumer electronics has the strong potential in shaping a new dimension of CE business in Pakistan. Moreover, the recent literature has strongly advocated for the scope of 5G IoT/IoUT. This is due to the fact that existing communication infrastructure will not be sufficient to handle modern day IoT/IoUT need. In this article, a comprehensive study on the scope of IoT/IoUT enabled consumer electronics business is presented. In addition, the rationale of 5G IoT/IoUT integration in the developing countries like Pakistan is discussed. Moreover, the threats and opportunities in the business of IoT/IoUT enabled CE devices are also been presented. Finally, this study submits the recommendations to establish IoT/IoUT enabled CE business in Pakistan. Â© 2019, Springer Science+Business Media, LLC, part of Springer Nature.